2009
DOI: 10.1111/j.1558-5646.2009.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Scapula Size and Shape in Didelphid Marsupials (Didelphimorphia: Didelphidae)

Abstract: The New World family Didelphidae, the basal lineage within marsupials, is commonly viewed as morphologically conservative, yet includes aquatic, terrestrial, scansorial, and arboreal species. Here, I quantitatively estimated the existing variability in size and shape of the Didelphidae scapula (1076 specimens from 56 species) using geometric morphometrics, and compared size and shape differences to evolutionary and ecologic distances. I found considerable variation in the scapula morphology, most of it related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 70 publications
8
59
0
Order By: Relevance
“…The overlap areas in morphometric cranial analyses using orthogonal matrix transformation techniques as PCA, irrespective of whether traditional or geometric, have also been identified in other species of other genera and in Calomys (Cordeiro-Estrela et al 2006, Astúa 2009, Bonvicino et al 2010, Martínez and Di Cola 2011. Furthermore, the results obtained in the present study for M1 shape are in agreement with those reported in other studies that showed a divergence in the shape of Calomys skull, but with small areas of intersection (Cordeiro-Estrela et al 2006.…”
Section: Discussionsupporting
confidence: 83%
“…The overlap areas in morphometric cranial analyses using orthogonal matrix transformation techniques as PCA, irrespective of whether traditional or geometric, have also been identified in other species of other genera and in Calomys (Cordeiro-Estrela et al 2006, Astúa 2009, Bonvicino et al 2010, Martínez and Di Cola 2011. Furthermore, the results obtained in the present study for M1 shape are in agreement with those reported in other studies that showed a divergence in the shape of Calomys skull, but with small areas of intersection (Cordeiro-Estrela et al 2006.…”
Section: Discussionsupporting
confidence: 83%
“…In Los Tuxtlas, the similarity between communities in P. opossum compared with D. marsupialis and D. virginiana dropped to approximately 50% (55 and 42%, respectively). The different diet composition of the 2 species of Didelphis relative to the gray four-eyed opossum may account for this difference (McManus, 1974;Castro-Arellano et al, 2000;Astú a, 2009).…”
Section: Taxonomic Similaritymentioning
confidence: 99%
“…This evolutionary event resulted in the diversification of some anatomical features that enabled marsupials to specialize in aquatic, terrestrial, scansorial, and arboreal lifestyles (Astú a, 2009). This allowed habitat segregation and the use of different dietary resources even in species occurring in sympatry (JulienLaferrière, 1991;Cá ceres et al, 2002;Cunha and Vieira, 2002;Gentile et al, 2004).…”
mentioning
confidence: 99%
“…McArdle and Rodrigo 1994;Martins and Hansen 1997;Garland et al 1999;Polly 2001;Rohlf 2001;Finarelli and Flynn 2006;Astúa 2009;Figueirido et al 2010;Almécija et al 2013;Figueirido et al 2013;Martín-Serra et al 2014a,b) using the square-changed parsimony method of Maddison (1991) with MorphoJ (Klingenberg 2011). We used this approach to specifically compare the elbow of Thylacoleo with the ancestral states of other mammalian groups and with other tips of the phylogeny.…”
Section: Borja Figueirido Et Al!12! !mentioning
confidence: 99%